Ecology–Economy Interface: Understanding Protected Area Awareness Among Forest-Fringe Dairy Farming Communities in Kerala - Sasikumar, Hridya; Maiti, Sanjit; Meena, H R; Vijayakrishnan, Sreedhar; Meena, B S (Indian Journal of Extension Education, 2025)
Dairy farming communities near protected areas (PAs) face challenges such as land-use restrictions, displacement, and human–wildlife conflict, often leading to negative attitudes and hindering sustainable agricultural development. Increasing awareness regarding PAs is essential to improve perceptions and promote coexistence with wildlife. This study assessed PA awareness and its determinants among 300 dairy farmers living near Silent Valley National Park, Wayanad Wildlife Sanctuary, and Karimpuzha Wildlife Sanctuary in Kerala, India, during 2023-24. Awareness was measured using a structured scale, and determinants were analysed with an ordinal logistic regression model. Farmers generally demonstrated moderate awareness of ecological roles but limited understanding of regulatory provisions and livestock-wildlife health concerns. Most farmers from Silent Valley, Wayanad, and the overall sample had a medium level of awareness, while a higher level of awareness was more common in Karimpuzha. Key predictors of awareness included gender, education, social participation, and information-seeking behaviour. The results highlight the need for targeted, gender-inclusive awareness programmes that promote community engagement, strengthen rural education, and encourage proactive information access.
Keywords: Awareness scale; Dairy farmers; Ecology; Human–wildlife conflict; Land use restrictions; Ordinal logistic regression; Protected area